Determination - Raatma L.; Awareness Publishing Group (Pty) Ltd (Gallo Manor: Awareness Publishing Group (Pty) Ltd, 2005)
Explains the virture of determination and describes ways to show it at home, at school and in the community.
Life Skills Education LIbrary-Character Education
Junior Non-Fiction-:Juvenile